PELATIHAN PEMBUATAN CLOUD STORAGE MENGGUNAKAN OWNCLOUD X DI UBUNTU SERVER PADA SISWA SMK MULTI KARYA MEDAN - Oris Krianto Sulaiman; Khairuddin Nasution; Muhammad Zulfansyuri Siambaton; Tasliyah Haramaini; Darjat Saripurna (Universitas Islam Sumatear Utara, 2021)
The purpose of the Workshop on Creating Cloud Storage using OwnCloud X on Ubuntu Server is to increase insight and knowledge to participants who come from students of SMK Multi Karya Medan.Ubuntu Server and Cloud Computing is a discussion that is often discussed at this time. From the results of the training, participants have been able to install their own Ubuntu Server, Web Server, PHP and Create OwnCloud.